Toxicity of Ivermectin Against the Larvae of Teak Defoliator, Hyblaea puera Cramer (Lepidoptera : Hyblaeidae) - Roychoudhury, N.; Joshi, K. C. (Indian Forester, 2010)
Toxicity of Ivermectin (Ivecop-12)-was evaluated against the larvae of a major defoliator of Teak, Hyblaea puera Cramer, during the outbreak period (July-August) in teak (Tectona grandis L.f.) forests of central India. The study was conducted once with eight treatments of higher (lethal) concentrations and then thrice with eight treatments of lower (lethal and sub-lethal) concentrations. Results revealed that ivermectin is highly toxic which could induce larval mortality when applied on host plant leaves and larvae together of the insect pest. Toxicity of ivermectin was found to be effective at ppm level and knock-down toxicity was noticed to be very rapid. Among the concentrations of ivermectin tested, cent per cent mortality was recorded by the higher concentrations up to 1172 ppm (0.001172%) and significantly different (P<0.01) from other treatments of lower concentrations including control. Further, there was a gradual decline of larval mortality with respect of lowering concentrations of the ivermectin. The LC50 value of the tested biological product was worked out to be 282 ppm (0.000282%) against the target insect pest.